ANALISIS FRAMING PEMBERITAAN COVID-19 DI ACEH - Junaidi; Siti Aisyah (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2021)
Since it was first discovered, news about the Corona virus (COVID-19) has graced various mass media pages, both print, electronic and online. Every day, we easily find various news about COVID-19 from various perspectives and framing certain issues. As is the case with the reports by Aceh.tribunnews.com, one of the online media in Aceh which is under Serambi Indonesia. This study focuses on examining the framing of news about the COVID-19 case in Aceh on the 17 August 2020 edition of Aceh.tribunnews.com media. This study uses a qualitative method with a descriptive analytical approach. Data was collected through observation and documentation, which were then analyzed using the Robert N Entman framing device. The results showed that, in reporting on the COVID-19 case in Aceh, Aceh.tribunnews.com selected and highlighted aspects related to the increasing number of COVID-19 in Aceh. The aspect of highlighting and emphasizing that Aceh.tribunnews.com is that the increase in COVID-19 cases in Aceh is due to community non-compliance with the application of health protocols. In addition, Aceh.tribunnews.com also pointed out the weakness of the Aceh Government and the COVID-19 task force in dealing with the spike in cases